Alteration of a Human Intestinal Microbiota under Extreme Life Environment in the Antarctica - Yamada, Shin; Touyama, Mutsumi; Yamazaki, Takashi; Benno, Yoshimi; Jin, Jong-Sik (Biological & pharmaceutical bulletin, 2014)
The human intestinal microbiota (HIM) settles from birth and continues to change phenotype by some factors (e.g. host’s diet) throughout life. However, the effect of extreme life environment on human HIM composition is not well known. To understand HIM fluctuation under extreme life environment in humans, fecal samples were collected from six Japanese men on a long Antarctic expedition. They explored Antarctica for 3 months and collected their fecal samples at once-monthly intervals. Using terminal restriction fragment length polymorphism (T-RFLP) and real time polymerase chain reaction (PCR) analysis, the composition of HIM in six subjects was investigated. Three subjects presented restoration of HIM after the expedition compared versus before and during the expedition. Two thirds samples collected during the expedition belonged to the same cluster in dendrogram. However, all through the expedition, T-RFLP patterns showed interindividual variability. Especially, Bifidobacterium spp. showed a tendency to decrease during and restore after the expedition. A reduction of Bifidobacterium spp. was observed in five subjects the first 1 month of the expedition. Bacteroides thetaiotaomicron, which is thought to proliferate during emotional stress, significantly decreased in one subject, indicating that other factors in addition to emotional stress may affect the composition of HIM in this study. These findings could be helpful to understand the effect of extreme life environment on HIM.